Central bank policy paths and market forward rates: A simple model - Ferre De Graeve; Jens Iversen (Sveriges Riksbank, 2015)
Increasingly many central banks announce likely paths for future policy rates. Recent experience suggest that market forward rates can differ substantially from those announced. Models commonly adopted in policy analysis ignore such differences. This paper studies a simple model that can capture deviations between announced paths and market forward rates. We detail the macroeconomic transmission of such deviations both in the model and in the data and show how the model can inform policy deliberations.
Keywords: E43; E44; E58; 330; Policy path; forward rate; forward guidance